ANALISIS PROFITABILITAS DAN LIKUIDITAS PADA KINERJA KEUANGAN PT MAYORA INDAH TBK PERIODE 2021-2023 - Dwi Utami Dias Tuti; Hasanah Setyowati (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This study aims to analyze the financial ratio and financial performance of PT Mayora Indah Tbk in 2021 to 2023 based on calculations on the profitability ratio and liquidity ratio. This study applies a descriptive method with a qualitative approach. The data collection technique in this study is documentation with secondary data sources, namely the annual financial report of PT Mayora Indah Tbk listed on the IDX. The results of the calculation of financial performance at PT Mayora Indah Tbk in the 2021-2023 period based on profitability from return on assets are stated to be less than good and return on equity is stated to be less than good, while liquidity from the current ratio is stated to be good and the quick ratio is stated to be good. The conclusion of financial performance at PT Mayora Indah Tbk in the 2021-2023 period in terms of profitability is said to be less than good and liquidity is said to be good.